STRUKTUR KOMUNITAS FITOPLANKTON DI PERAIRAN DAM RAMAN, METRO, LAMPUNG - Putu Cinthia Delis; Aulia Insani; Herman Yulianto; Rara Diantari (Journal of Aceh Aquatic Sciences, 2021)
Dam Raman is a reservoir located in the Metro City of Lampung. These waters used for activities such as aquaculture (KJA) and tourism activities. The input of organic matter from aquaculture (KJA) and tourism activities can trigger eutrophication. Phytoplankton are organisms that are sensitive to changes in water quality and have an important role as the basis of the food chain. The purpose of this study was to examine the abundance and community structure of phytoplankton in the Dam Raman. The research was conducted in January – March 2020. Samples were taken from four research observation stations. The data collected include water quality, species composition and abundance of phytoplankton, diversity index, similarity index, and dominance index. The results of the observations showed that there were 7 classes of phytoplankton. These classes include Chlorophyceae, Chrysophyceae, Cyanophyceae, Bacillariophyceae, Euglenophyceae, Rhodophyceae, and Xantophyceae. The abundance of phytoplankton ranged from 116-7278 cells/L. Phytoplankton diversity in Dam Raman is high with moderate community stability with values ranging from 2.89 to 3.33 and there is no indication of the dominance of certain types of phytoplankton